The proportion of cleaved anti-Müllerian hormone is higher in serum but not follicular fluid of obese women independently of polycystic ovary syndrome. Issue 6 (December 2020) - Peigné, Maëliss; Pigny, Pascal; Pankhurst, Michaël W.; Drumez, Elodie; Loyens, Anne; Dewailly, Didier; Catteau-Jonard, Sophie; Giacobini, Paolo
Abstract: Research question: Does the relative distribution of anti-Müllerian hormone (AMH) isoforms differ between patients depending on their body mass index (BMI) and polycystic ovary syndrome (PCOS) status in serum and follicular fluid? Design: Obese and normal weight patients (PCOS [ n  = 70]; non-PCOS [ n  = 37]) were selected for this case-control study in the serum. Between 2018 and 2019, obese ( n  = 19) and normal weight ( n  = 20) women with or without PCOS who were receiving IVF treatment were included in the follicular fluid study. The bio-banked serums and follicular fluid were tested for total AMH (proAMH and AMHN, C combined) and proAMH using an automatic analyzer. The AMH prohormone index (API = [proAMH]/[total AMH]x 100) was calculated as an inverse marker of conversion of proAMH to AMHN, C, with only the latter isoform that could bind to the AMH receptor complex. Results: The API was not significantly different between controls and women with PCOS, whereas obese women had a lower API compared with their normal weight counterparts. Grouping PCOS and controls, a lower API was found in obese versus normal weight women, suggesting a greater conversion of proAMH to AMHN, C . The API in the serum was significantly correlated with metabolic parameters. In the follicular fluid, API is not different between obese and normal weight women independently of PCOS and is higher than in the concomitant serum. Conclusions: The proportion of inactive form of AMH in the serum is higher in normal weight versus obese women but not in the follicular fluid, independently of PCOS. The conversion of proAMH into the cleaved isoform is likely to occur in extra-ovarian tissues and to exacerbate in obese individuals.